2013
DOI: 10.1104/pp.113.214528
|View full text |Cite
|
Sign up to set email alerts
|

Potential Functional Replacement of the Plastidic Acetyl-CoA Carboxylase Subunit (accD) Gene by Recent Transfers to the Nucleus in Some Angiosperm Lineages    

Abstract: (M.A.) Eukaryotic cells originated when an ancestor of the nucleated cell engulfed bacterial endosymbionts that gradually evolved into the mitochondrion and the chloroplast. Soon after these endosymbiotic events, thousands of ancestral prokaryotic genes were functionally transferred from the endosymbionts to the nucleus. This process of functional gene relocation, now rare in eukaryotes, continues in angiosperms. In this article, we show that the chloroplastic acetyl-CoA carboxylase subunit (accD) gene that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 84 publications
(114 reference statements)
5
87
1
Order By: Relevance
“…These questions extend to the entire ACCase complex, as we found evidence of gene loss/decay in nuclearencoded S. paradoxa ACCase genes (i.e., the apparent loss of ACCB1 and pseudogenization of ACCA). In at least two angiosperm lineages, the plastid accD gene has been transferred to the nucleus (Magee et al 2010;Rousseau-Gueutin et al 2013). However, we found no evidence of a functional nuclear copy of accD in any Silene species examined.…”
Section: Loss Of Plastid Heteromeric Accasecontrasting
confidence: 55%
See 1 more Smart Citation
“…These questions extend to the entire ACCase complex, as we found evidence of gene loss/decay in nuclearencoded S. paradoxa ACCase genes (i.e., the apparent loss of ACCB1 and pseudogenization of ACCA). In at least two angiosperm lineages, the plastid accD gene has been transferred to the nucleus (Magee et al 2010;Rousseau-Gueutin et al 2013). However, we found no evidence of a functional nuclear copy of accD in any Silene species examined.…”
Section: Loss Of Plastid Heteromeric Accasecontrasting
confidence: 55%
“…Furthermore, even in species with typical, slow-evolving plastomes, it is primarily the catalytic C-terminal domain of AccD that is highly conserved, whereas the N-terminal domain, which is plant-specific and has an unknown function, accumulates substantial structural divergence (Greiner et al 2008a). The evolution of accD is further complicated in some angiosperm lineages by functional transfer to the nucleus (Magee et al 2010;Rousseau-Gueutin et al 2013) or by functional replacement with a duplicated and retargeted copy of the homomeric ACCase (Konishi and Sasaki 1994). In contrast, there is no evidence (to our knowledge) of functional transfer of clpP1 to the nucleus in green plants.…”
Section: Discussionmentioning
confidence: 99%
“…1480 bp for taxa in this study) that has been lost from plastid genomes of some angiosperm families (Rousseau-Gueutin et al 2013) including the two species representing Alismatales (Spirodela polyrhiza and Colocasia esculenta) and the three species included in this study from Liliales (Smilax china, Veratrum patulum, and Fritillaria taipaiensis). In some cases accD and infA have been reported as transferred to the nuclear genome (Millen et al 2001;Rousseau-Gueutin et al 2013). Other coding regions missing from the plastid genome of comparator species included psaJ and ycf1 (Smilax china), rps12, rpl20, and trnH-GUG tRNA (Spirodela polyrhiza), and rps16 (Veratrum patulum and Dioscorea elephantipes).…”
Section: Comparisons Among the Plastid Genomes Of Iris Gatesii And Otmentioning
confidence: 96%
“…Comparative genomics have shown that all four genes are retained in the plastid genomes of most angiosperms, including chlorophyll-deficient, parasitic species (dePamphilis and Palmer, 1990;Funk et al, 2007;Jansen et al, 2007). Several examples of essential chloroplast genes that relocated to the nucleus have also been described (Magee et al, 2010;Rousseau-Gueutin et al, 2013). The absence of ycf1 and ycf2 in grasses (Jansen et al, 2007) and the replacement of accD with a nuclear gene that targets functional protein back to the chloroplast (Konishi and Sasaki, 1994;Chalupska et al, 2008) remain to be explained.…”
mentioning
confidence: 99%